A Stability Classification System for the Dragline Dump Slope - Bharati A.K.; Ray A.; Rai R.; Shrivastva B.K. (My University, 2025)
Opencast mining method is one of the most productive mining methods available at present, which is generally associated with the removal and handling of a huge amount of overburden material. Hence it imposes a serious challenge of dump slope stability and that too, mainly in the case of internal dumps. The study is primarily focused on the stability of dragline dumps and the subsequent development of a rating system to classify the stability of dragline dump profiles. Initially, numerical simulation is executed through RS2 (Version 9.0) software, which is based on the finite element method. Thereafter, simulation results are used to perform the sensitivity analysis of various geometrical and strength parameters of the dump slope, and the two-factor interaction method is also incorporated into the analysis, this method included the dependency of closest parameters while calculating the sensitivity index, and thereafter, it is converted into the rating of each parameter. The strength parameter like the angle of friction and the geometrical parameter like slope angle of the bench between the coal-rib roof and dragline sitting level are assigned the highest rating value. Based on the overall rating of the dragline dump, the dump slopes are classified into various classes, viz., very safe, safe, vulnerable, unstable, and highly unstable. This classification proved to be handy in the quick estimation of the stability of the dragline dump and also gives an idea of designing optimum and safe dragline dump profiles. The developed classification chart has been validated by the previous research works and has found similar results. © 2021, Society for Mining, Metallurgy & Exploration Inc.